Extremism and militancy - Akhmetova, Elmira (2015)
Extremism is a reality today. In fact, extremism and violence are universal phenomena, it existed throughout human history. It does not belong to any specific religious or social or ethnic groups. It threatens all people, regions and religions. But humans, both in the West and the East, are becoming more radical at this point of time. The extremism of Islamophobia is growing in Europe for some reasons. The slogan of the freedom of speech today became a tool of extremism as well, as we observe in the happening related to Paris tragedy. We try to convince people that Islam is a peaceful religion, but, extremism is becoming widespread in the Muslim world as well for many reasons. The Arab Spring where people aimed to establish democracy and good governance has turned into a center of extremism across the Middle East and North Africa.